A comparative study of chain based routing algorithms in wireless sensor networks - Salim, Ahmed; Badran, Asmaa Ahmed (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Many routing algorithms for Wireless Sensor Networks (WSNs) are designed and presented in the literature. The main target of these algorithms is to improve the performance of WSNs. In this paper, a comparative study of chain-based routing algorithms has been done. In this study, we compare the performances of PEGASIS [3], COSEN [6], IECBSN [8], CHAIN-BASED [15], CRA [12] and EAPHRN [9] algorithms when the mobile base station (BS) is used. We perform analytical simulations in terms of network lifetime and average energy consumption.